Connecting Australian Masculinities and Culture to Mental Health: Men's Perspectives and Experiences. (April 2023) - Sharp, Paul; Oliffe, John L.; Bottorff, Joan L.; Rice, Simon M.; Schulenkorf, Nico; Caperchione, Cristina M.
Masculinities and culture are intertwined and have significant implications for men's mental health. This study aimed to explore influences of Australian masculinities and culture on men's mental health. Five focus groups were conducted with men ( N = 43) living in New South Wales, Australia. Three overarching themes were identified: (1) a history of strength and self-reliance: taketh as we are, she'll be right, (2) social and geographical divides: surrounded by men but never actually connecting, and (3) male socialisation and generational dissidence: not getting the wisdom from the men that have gone before me . Participants' perspectives and experiences offer a reference point and lens for understanding challenges and enhancing efforts to promote Australian men's mental health. Gender transformative program strategies are proposed to promote men's mental health and help-seeking.